Analisis Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Kepuasan Konsumen Produk Velg HSR di Alpha Racing Toko Velg Ban dan Sporing Mobil Kab. Karawang - Imam Pranoto, Hajid; Isyanto, Puji; Sumarni, Neni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to find out how consumer satisfaction is influenced by product quality and service quality of HSR wheel products at the Alpha Racing Tire and Car Spring Wheel Shop, Karawang Regency. Data was collected through a survey using a questionnaire to consumers who had used HSR wheel products at the shop. Linear regression analysis is used to test the relationship between the independent variables (service quality and product quality) and the dependent variable (consumer satisfaction). Consumer satisfaction with HSR wheel items is significantly influenced by the quality of the product and the quality of the service provided, according to research findings. The research results show that the coefficient of determination (R Square) test results are zero point five two four, which shows that around fifty-two point four percent of the variability in consumer satisfaction can be explained by service quality and product quality. These findings highlight the importance of high quality services and products in meeting consumer expectations and satisfaction in the auto wheel industry. There is also a discussion of management consequences and recommendations for further research.